Molecular and Phylogenetic Character Analysis of Tuna (Auxis rochei) Based on the CO1 Gene in the Waters of West Lombok - H. Mahrus; Syamsul Bahri; Darmawan, Rizky Ferdyanto; Zulkifli, Lalu (Jurnal Biologi Tropis, 2024)
Tuna Fish is a type of tuna with a medium body size and fair wide distribution in Indo-Pacific waters. The number of Tuna Fish species that have morphological similarities can cause misidentification. This study aims to determine the genetic and phylogenetic diversity between variations of Tuna Fish species in the West Lombok Waters. This research is an exploratory study with the object of research being a dataset of ingroup sequences of tuna and outgroup sequences from the same family. The amplification of fish samples used DNA primers targeting the CO1 gene, which resulted in a sequence length of approximately 650 bp. Sequence data were analyzed using MEGA XI software known from phylogenetic tree analysis shows that Tuna Fish from the waters of the West Lombok are closely related to Tuna Fish from the South China Sea and have a genetic distance of less than 3%.